3(k+2)-5(k-2)=-2k-4

Simple and best practice solution for 3(k+2)-5(k-2)=-2k-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(k+2)-5(k-2)=-2k-4 equation:


Simplifying
3(k + 2) + -5(k + -2) = -2k + -4

Reorder the terms:
3(2 + k) + -5(k + -2) = -2k + -4
(2 * 3 + k * 3) + -5(k + -2) = -2k + -4
(6 + 3k) + -5(k + -2) = -2k + -4

Reorder the terms:
6 + 3k + -5(-2 + k) = -2k + -4
6 + 3k + (-2 * -5 + k * -5) = -2k + -4
6 + 3k + (10 + -5k) = -2k + -4

Reorder the terms:
6 + 10 + 3k + -5k = -2k + -4

Combine like terms: 6 + 10 = 16
16 + 3k + -5k = -2k + -4

Combine like terms: 3k + -5k = -2k
16 + -2k = -2k + -4

Reorder the terms:
16 + -2k = -4 + -2k

Add '2k' to each side of the equation.
16 + -2k + 2k = -4 + -2k + 2k

Combine like terms: -2k + 2k = 0
16 + 0 = -4 + -2k + 2k
16 = -4 + -2k + 2k

Combine like terms: -2k + 2k = 0
16 = -4 + 0
16 = -4

Solving
16 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -x^3-5x^2=6x | | 35.50=1.7n+1.5 | | -4+10q=10q-8 | | 3p+2=-4 | | (9x-6)3power=9 | | 128-N=46 | | 6x^2-400=0 | | y=3x^4-2x^3+74x^2-50x-25 | | 25x^2+1=37 | | 6x^2-400=9 | | 4e=36 | | 2/3*54 | | (9-6)3=9 | | 5/6x-5/6=5 | | 5(3-x)+2(3-x)=14 | | 3a+b-45=2a+4b-465.23+-a+507.23b | | 2x+8x-20=90 | | 15x+8=2x+2 | | -3x+4=-5x-9 | | 1/2m+3 | | 2.16+2=72 | | 6+2/3y=-12 | | 3x-(7x-4)=5x-(2x+10) | | z/17=-19 | | 14-3/4x | | 4-3x=5(x+4) | | 3a+b-45=2a+4b+465.23+-a+507.23b | | 19=4y+7 | | 29+0.15x=20+0.25x | | 2x+3-5x=5x-15+6 | | (2x+1)(2x-1)=4x | | 4y+2=-8/3(8-12y) |

Equations solver categories